Constraining the shear strain in viscoelastic materials and utlization of the "incompressible" properties for damping treatment in hybrid joint interface module to improve their effect for vibration control in machining. Issue 5 (March 2016) - Fu, Qilin; Rashid, Amir
Abstract A hybrid joint interface module (HJIM) was developed using viscoelastic materials' (VEM) "incompressible" property. The HJIM composes VEM layers compressed by screws. Its static stiffness and damping had been characterized by inverse receptance method. The analysis result showed that its static stiffness increases by nearly 50 % with increasing compression preload without compromising its loss factor. A comparison study of HJIM with a viscoelastic material joint interface module (VJIM) revealed that the change of the screws mechanical contact conditions affected the HJIM's stiffness. Compression preload by fastening the screws, however, did not significantly affect the damping property of the HJIM. On the contrary to shear pre-strain, compression preload did not affect the VEM's properties shown by studying the VJIM case. A workpiece was studied while fixed on the HJIM. Varying compression preload affected the stiffness of HJIM and that resulted in increased shear strain in VEM for certain modes while decreased shear strain in VEM for other modes. The affected shear strain in VEM altered the vibrational strain energy distribution and changed the receptance amplitude of different modes. In addition to apply the VEM where it is significantly strained, the analysis revealed that constraining the shear strain in VEM resulted in reduced receptance amplitude for different modes. The changes of receptance will further affect the vibration conditions in machining.